Is the Risk of Autism in Younger Siblings of Affected Children Moderated by Sex, Race/Ethnicity, or Gestational Age?. Issue 8 (October 2016) - Xie, Fagen; Peltier, Morgan; Getahun, Darios
ABSTRACT: Objective: To evaluate the recurrence risk of autism spectrum disorders (ASD) in younger siblings of affected children and determine how it is modified by race/ethnicity and sex. Method: Medical records of children born in a large health maintenance organization (Kaiser Permanent Southern California) hospitals from January 1, 2001, through December 31, 2010, and who remained in our system until 2 to 11 years of age were used to assess the risk of recurrence of ASD in younger siblings. Children born at <28 or >42 weeks gestation, multiple births, or those who were not active members for ≥3 months were excluded. ASD diagnosis was ascertained from DSM-IV codes, and the magnitude of the association was estimated using adjusted relative risks (aRRs). Results: Among eligible younger siblings, 592 (1.11%) had the diagnosis of ASD. The ASD rates were 11.30% and 0.92% for younger siblings of older affected and unaffected siblings, respectively (aRR: 14.27; 95% confidence interval, 11.41–17.83). This association remained after adjusting for potential confounding factors. Race/ethnicity- and gestational age-specific analyses revealed a positive association of similar magnitude across groups. Risk remained higher in younger boys than girls regardless of the sex of affected older siblings. Conclusion: The findings of this study suggest that the risk of ASD in younger siblings is higher if the older sibling has ASD. The risk of ASD in younger siblings of older affected siblings was comparable across gestational age at birth and child's race/ethnicity groups. However, risk remains higher for boys. This study contributes to a better understanding of the influence of race/ethnicity, sex, and gestational age at birth in identifying children at higher risk of ASD.